ANALISIS MOTIVASI KERJA PADA PT. MARKONI MANDIRI PERKASA - Fadil Abdilah; Asep Jamaludin; Nandang Nandang (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine work motivation and what indicators affect work motivation on employees of PT Markoni Mandiri Perkasa, this study uses descriptive writing method. The data collection technique is by observing and interviewing the employees of PT Markoni Mandiri Perkasa. The results of this study indicate that the employee's work motivation has not been good in terms of several indicators. Employees of PT Markoni Mandiri Perkasa are not yet responsible for their work. Employee performance has not been maximized. Opportunities to advance in the company are minimal because the company is not yet stable and is classified as a medium/small company. Employees feel comfortable at work because the company has given the rights and obligations of employees. Employees do not feel challenged because the applicable SOP have never been updated. While the implications of this research for the company must immediately evaluate the lack of employee motivation that can hinder the achievement of sales targets and customer satisfaction.